IDENTITAS MAKROSKOPI, MIKROSKOPI, KIMIAWI, RIMPANG C. Mangga, C. Zedoaria, DAN K. Rotunda - Sri Mulyani; Novia Dwi Nugraheni; Hendri Marinda Sari; A. Zulvita Anani Siswondo (Majalah Obat Tradisional, 2013)
Zingiberaceae plants in Indonesia has been widely used as traditional medicine, such as Curcuma mangga, C. zedoaria, and Kaempferia rotunda. These three plants known as the temu putih. This study aims to determine the chemical content, macroscopic and microscopic characteristics, in order to obtain characteristics of each of these plants as an aid for identification. Macroscopic examination is conducted by observing the characteristics of the rhizome in both fresh and dried state, while the microscopic examination is done by observing the microscopic characteristics of the powder and fresh rhizome. Examination of the essensial oil is conducted to determine phytochemical compound by using GC-MS method. Result shown these three specimens, macroscopically have different taste and smell. Microscopically, these three specimens have different cork thickness, secrete cell colors, and different amylum size. As identity compound, for C. mangga, C. zedoaria, and K. rotunda oils are mirsena, germakrona and benzilbenzoat respectively.